The relationship between abuse and neglect and adolescent suicidality: A moderated mediation model - Chang, Hongjuan; Yao, Zhenzhu; Zhang, Yu; Chen, Jiaqi; Shi, Peipei (Frontiers in Psychology, 2022)
Abuse and neglect can lead to suicide in adolescents; however, the internal mechanisms between abuse and neglect and suicidality remain unclear. We hypothesized that abuse and neglect could affect adolescent suicidality, and that mediating and moderating mechanisms exist between these two variables. We tested the mediating effects of stressful life events (misunderstanding and discrimination by others, poor academic performance, failed exams, interpersonal problems, and school punishment) on suicidal tendencies and moderating effects of resilience among 5,852 adolescents from 37 middle schools in five provinces of North, south, East, west, and central China. We used a questionnaire to collect data and adopted structural equation modeling to verify the correlation, mediating, and moderating effects among the variables. The results showed that stressful life events mediated the relationship between abuse, neglect, and suicide. Furthermore, resilience moderated the direct effect and second half of the mediating effect.